Hubungan Antara Technology Acceptance Model, User Satisfaction, User Trust dan Mobile Banking Adoption Intention pada Pengguna Layanan BNI Mobile Banking - Aurelio Putra Subani, Muhammad; Ratna Roostika, Raden Roro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study explores the relationship between the Technology Acceptance Model (TAM), consisting of perceived usefulness, perceived ease of use, and perceived security, with user trust, user satisfaction, and intention to continue adopting the use of mobile banking services among users of BNI Mobile Banking. The research sample involves users of BNI Mobile Banking in Kudus Regency, and data were collected by distributing questionnaires to 200 respondent offline at Bank Nasional Indonesia (BNI) branch in Kudus. Subsequently, data analysis was conducted using the Structural Equation Modeling (SEM) method with Excel and Smart-PLS software. The research findings indicate that perceived usefulness and perceived ease of use have a positive and significant impact on the intention to adopt mobile banking among users of BNI Mobile Banking. In contrast, perceived security does not have a significant influence on the intention to adopt mobile banking. User satisfaction and user trust also have a positive and significant impact on the intention to adopt mobile banking. Although the perception of ease of use does not significantly affect user satisfaction and user trust, these findings provide valuable insights into understanding the factors influencing the adoption and satisfaction of users in BNI Mobile Banking services.